Pengaruh Inventarisasi Aset, Legal Audit Dan Penilaian Terhadap Optimalisasi Aset Tetap (Studi Pada PT Pelindo 1 (Persero)) - Zainuddin; Eka Nurmala Sari; Widia Astuty (LPPM POLITEKNIK LP3I BANDUNG, 2023)
The purpose of this research is basically to be able to find out, test and analyze the effect of asset inventory, legal audit, and assessment on the optimization of fixed assets at PT Pelindo 1 (Persero). This research is an explanatory research focusing on the disclosure of causal relationships between variables using a quantitative approach. Data analysis used the SEM-PLS approach. The research findings produce: First, asset inventory has a significant effect on Asset Optimization at PT Pelindo 1 (Persero) in a positive direction. Second, the legal audit has a significant effect on Asset Optimization at PT Pelindo 1 (Persero) in a positive direction. Asset valuation has a significant effect on Asset Optimization at PT Pelindo 1 (Persero) in a positive direction. To be able to improve asset optimization at PT Pelindo 1 (Persero), the inventory process, legal audit and asset valuation are very important. This increase will have a good impact on increasing value for companies that are conducting IPOs and those that are already listed and increasing the stock market price. In addition to the improved economic value, the level of legality of assets is also increasingly optimal and has a positive effect on the company.